Liquid Self-Balancing Device Effects on Flexible Rotor Stability - Leonardo Urbiola-Soto; Marcelo Lopez-Parra (Shock and Vibration)
Nearly a century ago, the liquid self-balancing device was first introduced by M. LeBlanc for passive balancing of turbine rotors. Although of common use in many types or rotating machines nowadays, little information is available on the unbalance response and stability characteristics of this device. Experimental fluid flow visualization evidences that radial and traverse circulatory waves arise due to the interaction of the fluid backward rotation and the baffle boards within the self-balancer annular cavity. The otherwise destabilizing force induced by trapped fluids in hollow rotors, becomes a stabilizing mechanism when the cavity is equipped with adequate baffle boards. Further experiments using Particle Image Velocimetry (PIV) enable to assess the active fluid mass fraction to be one-third of the total fluid mass. An analytical model is introduced to study the effects of the active fluid mass fraction on a flexible rotor supported by flexible supports excited by bwo different destabilizing mechanisms; rotor internal friction damping and aerodynamic cross-coupling. It is found that the fluid radial and traverse forces contribute to the balancing action and to improve the rotor stability, respectively.